Mapping potential solvents for inhibitors removal from sugarcane bagasse hemicellulosic hydrolysate and its impact on fermentability - Nascimento, Viviane Marcos; Ienczak, Jaciane Lutz; Boni, Rafael; Maciel Filho, Rubens; Rabelo, Sarita Cândida [UNESP] (Elsevier, 2023)
Liquid[sbnd]liquid extraction as a detoxification process can increase productivity and product titers from lignocellulosic biomass fermentable sugars while leading to inhibitors recovery for further upgrading in sustainable chemical platforms. In this study, 14 solvents were investigated for inhibitors compounds removal. In addition to solvent solubility in hemicellulosic hydrolysate (HH) and distribution coefficients, solvent biocompatibility with S. passalidarum was determined. Considering all solvents evaluated, methyl isobutyl ketone (MIBK) showed good acetic acid (35%), furfural (42%), phenolic (35%), hydroxymethylfurfural (76%), and formic acid (18%) extraction. The medium presented lower HH solubility (0.93 ± 0.08 gsol LHH−1), which provided an ethanol yield (82.2 ± 0.6%), and productivity (0.90 ± ≤ 0.1 gEtOH L−1 h−1) higher than those of the synthetic media (control) (79.6 ± 0.3% and 0.89 ± ≤ 0.1 gEtOH L−1 h−1). In addition, preliminary evaluation of the solvent health-safety-environment pointed to MIBK as one of the solvents with the least impacts on climate change and human toxicity.
Keywords: Biocompatibility; Hemicellulosic hydrolysate; Liquid3liquid extraction; Partition coefficient; Pentose fermentation; Sugarcane bagasse